Cytomegalovirus disease in inflammatory bowel disease: epidemiology and disease characteristics in a large single-centre experience. Issue 11 (November 2016) - Bontà, Jonas; Zeitz, Jonas; Frei, Pascal; Biedermann, Luc; Sulz, Michael C.; Vavricka, Stephan R.; Scharl, Sylvie; Fried, Michael; Rogler, Gerhard; Scharl, Michael
Abstract : Background: Patients with inflammatory bowel disease (IBD) show an increased risk of developing cytomegalovirus (CMV) disease because of immunosuppressive medication and malnutrition. Here, we aimed to investigate the prevalence and clinical characteristics of CMV disease in our cohort of IBD patients. Patients and methods: We carried out a retrospective analysis of 1023 IBD patients treated at our IBD clinic at the University Hospital Zurich between 2007 and 2014. CMV disease was defined as a positive immunohistochemistry for CMV and 14 patients were identified. Results: The prevalence of CMV disease in our IBD cohort was 1.37%. Twelve patients had ulcerative colitis and two had Crohn's disease with colonic involvement. All patients who developed CMV disease received immunosuppressive medication or, as in one case, had HIV infection. The most used immunosuppressive medications were steroids and azathioprine. The most common therapeutic strategy was the consecutive use of ganciclovir and valganciclovir. Ten patients recovered and two were treatment refractory; among these, one required colectomy and two had a relapse. Conclusion: CMV disease may influence the clinical course of IBD. There is probably an association between CMV disease and IBD-specific medication. Risk factors, epidemiology and therapeutic strategy need to be further investigated.